Dose-Dependent Effects of Herbal Extract on Reproductive Health: Implications for Ovarian Structure, Organ Weight and Hormonal Balance in Female Rats - Ammari, Aiman; Alhimaidi, Ahmad; Amran, Ramzi; Aljawdah, Hossam; Murshed, Mutee; Rady, Ahmad (Indian Journal of Pharmaceutical Education and Research)
Aim: Investigate the impact of varying dosages (100 mg and 250 mg/kg) of a specific herbal extract on reproductive parameters in female albino rats. Background: Herbal extracts are extensively utilized in traditional medicine for their possible therapeutic advantages, including the promotion of reproductive health. The effects of different dosages on reproductive function are little comprehended. Materials and Methods: This research examines the dose-dependent impacts of a particular herbal extract on ovarian histology, reproductive organ weights and hormonal profiles in female rats. Female albino rats received varying dosages (100 mg and 250 mg\kg) of the extract, followed by an examination of ovarian morphology, reproductive organ weights (ovary, uterus and oviduct) and hormone concentrations (FSH, LH and estrogen). Results: The findings demonstrated a substantial dose-dependent response, where increased dosages resulted in marked ovarian follicular degeneration, decreased organ weights and modified hormone levels, suggesting possible detrimental impacts on reproductive health. These findings underscore the intricate equilibrium between therapeutic efficacy and toxicity, highlighting the necessity for meticulous dose consideration in the utilization of herbal extracts for reproductive health. Conclusion: The study offers essential insights into the safety and efficacy of herbal medicines, highlighting the necessity for more research to enhance their application.
Keywords: Dose-dependent effects; Female rats; Herbal extract; Hormone levels; Ovarian histopathology; Reproductive health.